REDEFINING GOLPUT IN THE LENS OF LAW: EXAMINATION OF ISLAMIC AND POSITIVE LAW - Robbish Thovani, Muhammad; Syihabuddin, Muhammad (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
In a democratic context that continues to travel, the phenomenon of the White Group (Golput) becomes a prolonged politics. This study aims to reveal the history of the Golput, the meaning of the Golput, and the response between Islamic law and the state regarding the phenomenon. Researchers recognize that Golput is a complex phenomenon that refers to various factors, such as political identity, community polarization, and inter-paradigm conflicts. In this study, the researcher tries to understand the dialectics between Islamic law and the state as an important foundation in studying the Golput phenomenon. It is hoped that this research will become a discourse and critical analysis as a response to the birth of the intended white group. This study uses the literature method by examining literature sources in the form of scientific articles as primary sources and books with similar themes as secondary sources. The results of this study revealed: that Golput became a controversial phenomenon that triggered the birth of Islamic law and the state. Islam and the state agree that the community must take part in political participation by considering the aspects possessed by the leader in the form of fairness, trustworthiness, and so on. The same was also found through the MUI fatwa which forbids Golput with several supporting arguments. Likewise, the interpretation of the Qur'an regarding compliance with policies issued by the government by considering aspects that are under commendable traits.